HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA TANGAN TERHADAP HASIL SERVIS TENIS MEJA SISWA EKSTRAKURIKULER SMA NEGERI 1 KUNTO DARUSSALAM KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Riang Perdana Putra; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: The problem of this research is the lack of maximum tenis meja service at the SMA Negeri 1 Kunto Darussalam extracurricular student that caused by the lack of wrist flexibility and hand eye coordination. The purpose is to find out how big the relationship of wrist flexibility and hand eye coordination to the tenis meja service result of SMA Negeri 1 Kunto Darussalam extracurricular student. The kind of this research is correlation research that used to compare a measurement two different variables in order to determination the relationship between those variables. The population in this research is amount to 12 people that consists of 8 male students and 4 female students. Sampling technique is using purposive sampling technique that is considering to the research purpose that amount to 8 male students. The instrument of this research is wrist flexibility test, tennis ball catch-throw test, and service test. Data test is using normality test, product moment correlation test, significant test α = 0.05. Normality test variable X1, L0maks (0,1807) < Ltabel (0,2850), X2 L0maks (0,1544) < Ltabel(0,2850) and normality test variable Y, L0maks (0,1492) < Ltabel (0,2850) in the other words normal data and the research conclusion shows: there is significant relation between wrist flexibility and hand eye coordination to the tenis meja service result with correlation r= 0.990 which rhitung > rtabel or 0.990 > 0,754 and the relationship is categorized as strong, thereby Ha is accepted.Key Words: Relationship, Wrist Flexibility, Hand Eye Coordination, Service Result